NILAI KARAKTER BANGSA DALAM SERAT BRATAYUDA SADURAN KAREL FREDRIK WINTER - Yoga Yolanda; Endang Sri Widayati; Furoidatul Husniah (Universitas Negeri Makassar, 2018)
Abstrak: Nation Character Values in Serat Bratayuda Adapted by Karel Fredrik Winter. This study aims to explain the nation character values in serat bratayuda obtained from the characters. This study used a qualitative approach with descriptive research type. Data collection techniques is documentation with data sources in the form of serat Bratayuda adapted by Karel Fredrik Winter. The data are words, sentences, and/or paragraphs in the serat bratayuda that indicate the appearance of characters. Through this research found seven nation cultural and characters values through dialogue and narration in Serat Bratayuda, i.e: (1) cinta tanah air, (2) cinta damai, (3) jujur, (4) pekerja keras, (5) kreatif, (6) tanggung jawab, dan (7) religius.